Comprehensive study of ovarian tumours in Kathmandu University Hospital - Tamrakar, Suman Raj; Makaju, Ramesh; Shrestha, Abha; Kayastha, Suresh (Journal of Kathmandu Medical College, 2018)
Background: Ovarian tumours account for 15% to 25% of all primary malignancy and the leading cause of death from gynaecolgical malignancies. There are limited publications related to ovarian tumours from Nepal. Ovarian related surgeries are the common surgeries in Kathmandu University Hospital. This study aims to provide basic information related to ovarian tumours from this geographical region of Nepal.Objectives: To review the nature of ovarian problems and certain socio-demographic information namely: caste, age, address and co-morbid condition of the patients presenting with ovarian problems.Methodology: This is a retrospective study of patients seeking surgical treatment of ovarian lesions in Kathmandu University Hospital from January 1, 2011 to June 30, 2018. This study was undertaken by reviewing the inpatient, outpatients and OT records in the Department of Obstetrics and Gynaecology and the records from Department of Pathology. All the files and computer records were reviewed and analyzed for nature of ovarian problems and certain demographic variables.Results: Out of the 860 cases, about 61% were non-neoplastic while benign ovarian tumours and malignant ovarian tumours were 35% and 3.7 % respectively. Almost one third of the cases were of Brahmin/Chhetri (37.3%) and 58.3% of the patients were from Kavre district. Mean age of the patients with ovarian problems was 34.89±11.15 years (range 12-72 years). There was no statistically significant difference between the mean age of patients with non-neoplastic ovarian lesions and neoplastic ovarian lesions (p value = 0.3371). There was statistically significant difference between the mean age of patients with benign ovarian tumours and malignant ovarian tumours (p value = 0.0001). And malignant ovarian tumours were significantly high among patients above 41 years in comparison to benign ovarian tumours of same age group (p value = 0.0008). Out of 32, ten malignant ovarian tumours occurred in relatively young age group. Of the 860 ovarian lesions, 438 and 422 ovarian lesions were removed through open technique and laparoscopic techniques respectively. Mature cystic teratoma (64.1%) was the commonest benign tumor and serous cyst adenocarcinoma (43.8%) was the commonest malignant tumour in this study.Conclusion: Ovarian tumours are one of the gynaecological diagnoses in Kathmandu University Hospital. If only ovarian neoplasms are considered, most of the ovarian tumours are benign and few are malignant. Minimal invasive surgeries are possible, except that for malignant ovarian tumours.